Stability and safety of ships regulation and operation - Kobylinski, Lech K.; Kastner, Sigismund (Elsevier ocean engineering book series, 2011)
A stability accident is one of the worst things that can happen to a ship. This two-volume set is intended for those concerned with the prevention against capsizing. It focuses on the regulatory, operational aspects of intact stability, and provides a review of research and results in the field.